Manfaat Tai chi terhadap Pasien Penyakit Paru Obstruksi Kronis - Qurratu Iffoura; Agung Waluyo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
The prevalence of Chronic Obstructive Pulmonary Disease (COPD) continues to increase in the world and predicted in 2030 to rank third in the world. COPD causes people to have difficulty breathing, limit mobility and lifestyle, and can cause more serious complications and lead to a decrease in quality of life. One of the nonpharmacological treatments that can be done is Tai chi a traditional Chinese mind-body exercise. Objective: This literature study aims to describe benefits of Tai chi in improving the quality of life of patients with COPD. Literature review was conducted from various sources such as CINAHL, MEDLINE, science Direct and proquest. Tai chi was a meditative martial art consisting of three basic concepts namely physical exercise, breathing techniques, and full awareness. Tai chi movements that were practiced vary, such as 24 movements which were or 6 movements that have been modified and simplified. Some of the benefits of doing Tai chi include increased muscle strength, reduced tightness, improved pulmonary function, increased 6-minute walk distance (6MWD) and increased St. George’s Respiratory Questionnaire (SGRQ) scores. Tai chi can be used as a complementary therapy in COPD patients according to their preferences and values. In addition this exercise can be recommended in patients with other chronic diseases. Keywords: Tai chi; COPD; complementary therapy ABSTRAK Prevalensi Penyakit Paru Obstruksi Kronis (PPOK) terus meningkat di dunia dan diprediksikan pada tahun 2030 akan menempati urutan ketiga di dunia. PPOK menyebabkan penderita sulit bernafas, membatasi mobilitas dan gaya hidup, serta dapat menyebabkan komplikasi yang lebih serius dan mengarah kepada penurunan kualitas hidup. Salah satu penatalaksanaan non farmakologis yang dapat dilakukan ialah Tai chi, latihan mind-body tradisional Tiongkok. Studi literatur ini bertujuan untuk menggambarkan manfaat Tai chi pada peningkatan kualitas hidup pada pasien PPOK. Penulusuran literature dilakukan dari berbagai sumber seperti CINAHL, MEDLINE, Science Direct dan proquest. Tai chi merupakan seni bela diri yang bersifat meditasi yang terdiri dari tiga konsep dasar yaitu latihan fisik, teknik pernapasan, dan kesadaran penuh. Gerakan Tai chi yang dipraktikkan bervariasi, seperti 24 gerakan Yang atau 6 gerakan yang telah dimodifikasi dan disederhanakan. Beberapa manfaat melakukan Tai chi seperti peningkatan kekuatan otot, mengurangi sesak, meningkatkan fungsi paru, meningkatkan 6-minute walk distance (6MWD) dan peningkatan skor St. George’s Respiratory Questionnaire (SGRQ). Tai chi dapat dijadikan terapi pelengkap pada pasien PPOK sesuai dengan preference dan nilai yang dimiliki individu. Latihan ini dapat direkomendasikan pada pasien penyakit kronis lainnya. Kata kunci: Tai chi; PPOK; terapi komplementer